A Field Guide to the Information Commons - Forrest, Charles; Halbert, Martin (Rowman & Littlefield Publishers, 2009)
Our sources of information, and the practices we use to find it, are in a period of rapid flux. Libraries must respond by selecting, acquiring, and making accessible a host of new information resources, developing innovative services, and building different types of spaces to support changing user behaviors and patterns of learning. A Field Guide to the Information Commons describes an emerging library service model that embodies all three spheres of response: new information resources, collaborative service programs, and redesigned staff and user spaces. Technology has enabled new forms of information-seeking behavior and scholarship, causing a renovation of libraries that revisits the idea of the "commons"—a public place that is free to be used by everyone. A Field Guide to the Information Commons describes the emergence, growth, and adoption of the concept of the information commons in libraries. This book includes a variety of contributed articles, and descriptive, structured entries for various information commons in libraries across the country and around the world.